2019
DOI: 10.1021/acs.est.9b04255
|View full text |Cite
|
Sign up to set email alerts
|

Method Development for Effect-Directed Analysis of Endocrine Disrupting Compounds in Human Amniotic Fluid

Abstract: The developing fetus represents a highly sensitive period of exposure to endocrine disrupting compounds (EDCs). However, risk assessment of EDCs is hampered by the lack of data on direct in utero exposure. In this study, we developed a robust analytical methodology for the identification of a wide range of known and unknown EDCs in full-term amniotic fluid (AF). First, a method for extraction and fractionation of a broad range of polar and nonpolar EDCs was developed and validated. Maximal recoveries of refere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Pregnant women are a unique population who are exposed to endocrine disruptors during pregnancy that can affect the baby through body fluids. Liquids such as urine, maternal milk, serum, and amniotic fluid are currently the most commonly used substances to assess the EDCs in the body [16,23]. Its widespread use has led to the detection of BPA in low doses in pregnant women.…”
Section: Detection Methodsmentioning
confidence: 99%
“…Pregnant women are a unique population who are exposed to endocrine disruptors during pregnancy that can affect the baby through body fluids. Liquids such as urine, maternal milk, serum, and amniotic fluid are currently the most commonly used substances to assess the EDCs in the body [16,23]. Its widespread use has led to the detection of BPA in low doses in pregnant women.…”
Section: Detection Methodsmentioning
confidence: 99%
“…The occurrence of PFASs in placenta, , umbilical cord blood, , amniotic fluid, , and infant serum indicated their prenatal exposure. Numerous studies have shown that there are extensive prenatal exposures to PFASs among pregnant women and infants.…”
Section: Levels Of Prenatal Exposure To Pfass Worldwidementioning
confidence: 99%
“…Concentration and Geographical Distribution of PFASs in Various Matrices. The occurrence of PFASs in placenta, 47,48 umbilical cord blood, 49,50 amniotic fluid, 50,51 and infant serum 52 studies have shown that there are extensive prenatal exposures to PFASs among pregnant women and infants.…”
Section: Levels Of Prenatal Exposure To Pfass Worldwidementioning
confidence: 99%
See 1 more Smart Citation
“…The placenta must develop for a pregnancy to be successful. This delicate organ comprises multiple layers of tissue that must develop normally during pregnancy to function correctly, which could have devastating consequences for the fetus ( 13 ). Different EDCs may indirectly influence the fetus through the placenta.…”
Section: Introductionmentioning
confidence: 99%